Strategic Planning of Information Systems at Leony Frozen Food Agents in Semarang Using Ward and Peppard Methods - Daniel Chris Petra Nabena; Hanna Prillysca Chernovita (Journal of Information System and Informatics, 2022)
Leony Frozen Food is a micro (small and medium) company that sells food in a frozen and cold temperature state located in Semarang. Leony Frozen Food still uses manual methods in carrying out its business process activities, and one example is doing bookkeeping. Leony Frozen Food does bookkeep still manually recorded in books and moved in the Android application, namely Cash Books. Therefore, IS/IT strategic planning is needed following the needs and current conditions of the company. This research aims to improve effectiveness and efficiency in carrying out business processes and providing solutions to problems in Leony Frozen Food. This study used data collection methods by interviewing company owners and direct observation to Leony Frozen Food. The methods used to conduct SI/IT strategic planning in this study used the Ward and Peppard methods, which included internal and external analysis of the company using Value Chain analysis, SWOT analysis, Porter's Five Forces analysis, and producing output in the form of IS/IT application proposals mapped using the McFarlan Strategic Grid. The results of IS/IT strategic planning are implemented in the next four years.